2017
DOI: 10.1016/j.watres.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the influence of water stagnation and temperature change on water quality in a full-scale domestic drinking water system

Abstract: The drinking water quality changes during the transport through distribution systems. Domestic drinking water systems (DDWSs), which include the plumbing between the water meter and consumer's taps, are the most critical points in which water quality may be affected. In distribution networks, the drinking water temperature and water residence time are regarded as indicators of the drinking water quality. This paper describes an experimental research on the influence of stagnation time and temperature change on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 64 publications
9
65
1
3
Order By: Relevance
“…Some of the recent water quality studies include: an assessment of trace elements in surface and ground water quality in the Ebocha-Obrikom oil and gas producing area of Rivers State, Nigeria by Raimi and Sabinus (2017) [1]; Morufu and Clinton, (2017) [2], water-related problems and health conditions in the oil producing communities in central senatorial district of Bayelsa State by Raimi et al (2017) [3], water quality on intermittent water supply by Erickson et al (2017) [4], major ion chemistry of the groundwater by Bikundia and Mohan (2014) [5], water quality due to temperature variation and water stagnation by Zlatanoviae et al (2017) [6], the use of fluorescence spectroscopy for tap water quality assessment by Heibati et al (2017) [7], Hydrochemical evolution and quality of groundwater by Jassas and Merkel (2015) [8], and evaluation of hydrogeology and groundwater quality by Edet (2016) [9]. Water quality was also studied in different areas of the world by Dhamodharan et al (2016) [10], Li et al (2016) [11], Nagaraju et al (2016) [12], Kumar et al (2017) [13], and Tiwari et al (2017) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent water quality studies include: an assessment of trace elements in surface and ground water quality in the Ebocha-Obrikom oil and gas producing area of Rivers State, Nigeria by Raimi and Sabinus (2017) [1]; Morufu and Clinton, (2017) [2], water-related problems and health conditions in the oil producing communities in central senatorial district of Bayelsa State by Raimi et al (2017) [3], water quality on intermittent water supply by Erickson et al (2017) [4], major ion chemistry of the groundwater by Bikundia and Mohan (2014) [5], water quality due to temperature variation and water stagnation by Zlatanoviae et al (2017) [6], the use of fluorescence spectroscopy for tap water quality assessment by Heibati et al (2017) [7], Hydrochemical evolution and quality of groundwater by Jassas and Merkel (2015) [8], and evaluation of hydrogeology and groundwater quality by Edet (2016) [9]. Water quality was also studied in different areas of the world by Dhamodharan et al (2016) [10], Li et al (2016) [11], Nagaraju et al (2016) [12], Kumar et al (2017) [13], and Tiwari et al (2017) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The biological stability of drinking water is critical for the safety of drinking water [1]. However, water quality can get degraded during distribution, causing hygienic, aesthetic, and operational issues [2]. In particular, microbial regrowth can deteriorate the safety of drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that both Bacteroides and Firmicutes are important in the fermentation reaction, e.g., the relative abundance of Bacteroides and Firmicutes in intestinal flora are closely related to fat deposition, and the ratio of the two (Bacteroidetes/Firmicutes) may be even more important [24]. Zlatanović research found that the total organic carbon (TOC) concentrations decreased with the stagnation time of two taps, as a commonly applied measure to indicate the natural organic matter (NOM) concentration in a water sample [4]. Meanwhile, Prest suggested that 1 µg/L of organic carbon is enough to stimulate the growth of 10 3 -10 4 cell/mL [25].…”
Section: Bacterial Phylamentioning
confidence: 99%
“…During stagnation, the pipe network acts like a giant stationary reactor, providing a continuous and stable environment for microorganism growth. This contributes not only to the augmentation of planktonic bacteria, but also to the growth of biofilms on the wall of the pipeline [4]. Furthermore, when the faucet is turned on after several days, biofilms which are not firmly attached will detach and fall into the flowing water and increase the health risks associated with microbes.…”
Section: Introductionmentioning
confidence: 99%